WELL, WELL, WELL: VARIATION IN DRESS VOWEL REALISATIONS BEFORE LATERAL /L/ IN AUSTRALIAN ENGLISH - Ounu Zakiy Sukaton (Lire Journal (Journal of Linguistics and Literature), 2020)
The ongoing el-æl merger in Australian English has been informally recognized by Australians especially those who have experience of contact with Victorians. This study aims to investigate the correlation of speakers’ sex and origin with their /el/ production and how speech styles influence their production. Two male speakers of Australian English from Victoria and South Australia were recorded while reading texts, doing interviews, and having casual conversations. The recordings were then transcribed and analyzed by using various software to describe their /el/ productions. The result of this study was both male subjects are able to produce considerable variations in their /el/ productions. The production of the Victorian male speaker confirmed the findings of previous studies while the SA male speaker showed variations of /el/ similar to back vowels. Speech styles do not significantly affect the variations of /el/ production. The ongoing merger of el-æl in Australian English might be spreading from Victoria through diffusion to its neighboring states. However, more studies should be conducted in order to confirm this suspicion. Other suggestions include customized reading passages and better semi-structured interviews.